2019
DOI: 10.1016/j.ejrad.2019.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative dynamic contrast-enhanced magnetic resonance imaging in epithelial ovarian cancer

Abstract:  Mean K trans values were higher in high-grade serous OC than in other types  Lower mean K trans values predicted residual tumor in sytoreductive surgery  Multiparametric MRI variables were predictive for recurrence free survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Yang et al (38) and Mayr et al (39) showed that DCE-MRI parameters derived from low-enhancement or poorly perfused areas were associated with poor post-treatment outcomes in cervical cancer, which is consistent with our findings. Lindgren et al (20) showed that the lower mean K trans value was correlated with the higher risk of residual tumor after cytoreductive surgery, which also support our results. In addition, studies had proven that other histogram parameters (SD, skewness, and 95th percentile) of K trans were helpful for differential diagnosis and the prediction of prognoses, which further confirmed the advantage of DCE-MRI histogram analysis in reflecting tumor heterogeneity (29,40,41).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Yang et al (38) and Mayr et al (39) showed that DCE-MRI parameters derived from low-enhancement or poorly perfused areas were associated with poor post-treatment outcomes in cervical cancer, which is consistent with our findings. Lindgren et al (20) showed that the lower mean K trans value was correlated with the higher risk of residual tumor after cytoreductive surgery, which also support our results. In addition, studies had proven that other histogram parameters (SD, skewness, and 95th percentile) of K trans were helpful for differential diagnosis and the prediction of prognoses, which further confirmed the advantage of DCE-MRI histogram analysis in reflecting tumor heterogeneity (29,40,41).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, the study by Lindgren et al. (20) showed DCE-MRI parameters can predict the clinical outcome in ovarian cancer by measuring simple mean values. To our knowledge, there have been no studies on DCE-MRI histogram analysis to predict EOC recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…In unclear cases a senior radiologist (SR) with 12 years of experience in gynecological imaging was available for consultation. Image analysis has been described in detail previously [22]. The perfusion parameter maps were generated automatically with NordicICE using pharmacokinetic modeling of contrast kinetics according to the Tofts model [28].…”
Section: Methodsmentioning
confidence: 99%
“…Conventional magnetic resonance imaging (MRI) is applied in the preoperative imaging of indeterminate ovarian tumors due to its superior soft tissue extraction. Dynamic contrast enhanced (DCE) sequence, utilizing contrast agent extravasation from blood flow to tissues, may not only be used to characterize benign lesions from malignant tumors [19,20] but may also provide additional information on the tumor prognosis [21,22] and treatment response [2325]. Pharmacokinetic perfusion parameters reflect the circulation physiology in the microvasculature and give quantitative parameters to compare flow and vessels permeability properties [2628].…”
Section: Introductionmentioning
confidence: 99%
“…BRCA mutations are present in approximately 14% of epithelial ovarian cancers. The poor mortality of this illness is attributable to diagnosis made at the terminal stage, accounting for approximately 70% of the total ovarian malignancies [2,3]. Contemporary research suggests that every histologic type of EOC is related to different morphologic and molecular mutations, such as endometroid, clear-cell, mucinous, and serous carcinomas [4][5][6].…”
Section: Introductionmentioning
confidence: 99%